Strategi Inovatif Pembelajaran Al-Qur’an Hadist Berbasis Kurikulum Merdeka di MTS Alwashliyah 16 Perbaungan - Izqi Meizzaluna; Yurmaini Yurmaini; Hotni Sari Harahap (HIBRUL ULAMA, 2025)
This study analyzes innovative learning strategies for Al-Qur’an Hadith based on the Merdeka Curriculum at MTs Al Washliyah 16 Perbaungan. Islamic education faces significant challenges from modernization, digitalization, and learning quality gaps, exacerbated by low technological readiness and the dominance of conventional methods. The research aims to explore and analyze the innovative strategies implemented by Al-Qur’an Hadith teachers within the Merdeka Curriculum framework, integrating local values and the spirit of the Al Washliyah organization. Employing a qualitative descriptive case study approach, data were collected through observations, interviews (teachers, students, vice-principal), and documentation. The findings indicate that the implementation of innovative strategies—including project-based learning (making video recitations of verses), differentiation, utilization of digital media (projectors, interactive quizzes), and the integration of Islamic and local wisdom values (Qur'an recitation, memorization of Surah As-Saff verses 10-11)—has been effective. These strategies successfully enhanced active participation, conceptual understanding, students' reflective skills, and character development in line with Merdeka Curriculum principles. However, implementation faces multidimensional challenges such as limited facilities, varied student readiness, resistance to new methods, and the need for more adequate training and institutional support.